Étude stylistique de la référenciation dans Le Chant du monde de J. Giono - Youssef El Yaacoubi (Multilinguales)
Our paper, aided by work in linguistics and stylistics, focuses on referential meaning and telescoping of a reality other than what is stated openly in the text. To do this, we chose the work of Jean Giono, a great creator of images and spaces, Le Chant du Monde, where the narrative incorporates the poetic dimension through different modes of representation, whether literary, poetic musical or pictorial. Furthermore, representation is transmuted by the magic of style and techniques in a reality that concerns the mythical intertext. In this, the landscape in Le Chant du Monde by Jean Giono, the description of the places in his bill incorporates the co-presence of the human and the animal in perfect harmony relating to myth and perceptions.